THE DIFFICULTIES OF BILINGUALISM (ENGLISH AND ARABIC) ON SPEAKING ABILITY FACED BY THE MEMBERS AT THE FIRST SEMESTER AT APK (ASRAMA PUTERI KHADIJAH) - Bukhory, Umar; Susanti, Feni (OKARA: Jurnal Bahasa dan Sastra, 2017)
The phenomenon of bilingualism happens around us. There are some people that acquire more than one language. The competency of using two languages in a communication is called billinguality. Billinguality deals with the language, and speaking is a part of language skills. APK (Asrama Puteri Khadijah) is a dormitory for college students of STAIN Pamekasan in which the members are required to speak using two languages (English and Arabic) in their daily activities. The problem raises, the members have some difficulties in keeping speaking English and Arabic in balance. Therefore, investigating the process of how the members of APK (Asrama Puteri Khadijah) speak bilingual, some difficulties for them to speak bilingual, and the strength and weaknesses of bilingualism for them are the focus of this study. A descriptive qualitative research is applied in this study. The three data collection procedures that were applied are observation, interview, and documentation. This study results that the process of bilingualism of the members of APK deepens on the concept of grammar understanding in English and Arabic Intensive class, memorizing vocabulary, MuhÄdhoroh program (formal situation), and how the members practice speaking English and Arabic in their daily communication. Some members used code switching, code mixing, and inference to solve their bilinguality problems on speaking. Furthermore, despite some problems, their mistakes of bilinguality is still understandable and communicative, however, the problems on the morphological, phonological, and syntactical levels are still unresolved.